2017
DOI: 10.1177/0025817217734091
|View full text |Cite
|
Sign up to set email alerts
|

Homicide concealed strangulation after bobbing reins in sexually sadistic homicide

Abstract: This case of sexually motivated homicide combined the perpetrator's obliteration of his victim's identity along with his attempt at concealment of the corpse and sexual gratification following ligature strangulation of a young unidentified female from a minority Indian state. Sexual bondage was evident with characteristic body tying in a typical posture to fuel the killer's sexual arousal and gratification before, during and then after strangling his victim with a scarf. The victim's body was left in a sack pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The authors previously reported on placing the body in a sack as being among the most vivid and rarest methods of homicide concealment. 11 However, the use of table salt in attempted murder concealment has been reported once to date. Here a mummified dead body of an old male soiled with mud and lumps of table salt was exhumed six years after murder.…”
Section: Discussionmentioning
confidence: 99%
“…The authors previously reported on placing the body in a sack as being among the most vivid and rarest methods of homicide concealment. 11 However, the use of table salt in attempted murder concealment has been reported once to date. Here a mummified dead body of an old male soiled with mud and lumps of table salt was exhumed six years after murder.…”
Section: Discussionmentioning
confidence: 99%